Janus Microswimmers: Oscillatory Light‐Emitting Biopolymer Based Janus Microswimmers (Adv. Mater. Interfaces 10/2020). Issue 10 (20th May 2020) - María‐Hormigos, Roberto; Escarpa, Alberto; Goudeau, Bertrand; Ravaine, Valérie; Perro, Adeline; Kuhn, Alexander
Abstract : An alginate based Janus particle, depicted as a floating sphere, contains Prussian blue as a bifunctional catalyst, decomposing hydrogen peroxide into oxygen bubbles, and catalyzing simultaneously the chemiluminescent reaction of luminol. This asymmetric character leads to a buoyancy driven periodic up and down motion of such a light emitting microswimmer. More details can be found in article number 1902094 by Adeline Perro, Alexander Kuhn, and co‐workers.